INTERPRETERS AND TRANSPORT SPECIALISTS’ APPROACHES TO TRANSLATION - Filimonova, Liliya (Журнал иностранных языков и лингвистики, 2023)
In 2022-23 academic year Tashkent State Transport University introduced new directions in education and one of them is ‘translation studies in transport sphere’.